Prediction of students academic achievement in unimap using data mining approach - Fatihah Aziz (Institute of Engineering Mathematics, 2016)
This study focuses on the students' academic performance in Universiti Malaysia Perlis. Factors that affect the students' academic performance have been investigated, such as age, gender, entry qualification, schools, entry cumulative grade point average value (CGPA), result for semester 1 and semester 2 and result of graduated CGPA.